MENGGAMBAR SEBAGAI EKSPRESI VISUAL PADA PESERTA DIDIK KELAS V SDN PANDEAN LAMPER 05 - Yuniar Sekar Syaharani, Inka; Prima Artharina, Filia; Adhi Prasetyo, Singgih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is motivated by the importance of drawing activities as a medium of visual expression for elementary school students in art learning. Referring to (Priyanto, 2020: 165), drawing serves as a means for students to illustrate imagination, convey experiences, and express their desires and feelings. This study aims to analyze the prosess and outcomes of visual expression in drawing activities among fifth-grade students of SDN Pandean Lamper 05. This research employed a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation, involing 15 students as research subjects. The results indicate that the process of visual expression consists of several stages, namely providing stimulus, developing ideas, sketching, developing drawings, and presenting the artwork. The findings also show that students’ artworks reflect both similarities and variations of ideas influenced by their experiences and imagination. Furthermore, the use of art elements is dominated by lines and shapes, while art principles such as unity and balance begin to emerge, although still in a simple form. Variations in color usage are also identified, influenced by students’ technical abilities and self-confidence. In conclusion, drawing activities function as a medium of visual expression that reflects students’ experiences, feelings, and imagination, and highlight the importance of supporting creative freedom and gradually improving students’ technical skills in art learning.